EVALUASI KETAHANAN SEPULUH AKSESI JAMBU METE TERHADAP PENYAKIT BUSUK AKAR FUSARIUM - Supriadi, Handi; Taufik, Efi; Harni, Rita (Jurnal Tanaman Industri dan Penyegar, 2011)
Evaluation of resistancies of ten accessions of cashew to fusarium root rot disease. Cashew is a commodity that has an important role in improving the welfare of farmers, especially in areas with dry climates and poor nutrients. One obstacle in the development of cashew nut is the presence of FusariumÂ  attacks that can shut down the plant in the nursery. Research evaluation of resistancies of ten accessions of cashew against Fusarium root rot disease, which aimed to get the accessions that resistant to Fusarium root rotdisease has been conducted in the Laboratory and Greenhouse of Indonesian Spices and Industrial Crops Rresearch Institute (ISICRI) January to December 2009. Research using completely randomized design with 10 treatments and three replications. Treatments were the type of accsession namely Arsyad Labone, Sri Lanka,JT-21, Laode Head, Laode Gani, Sleman Red, Nigeria, Laode Kase, JN 26, NDR-31. The result obtained one cashew accessions highly resistant namely JN-26, and two accessions that resistant that is Laode Gani, and Sleman Red with root rot disease incidence of each 0; 6.67, and 9.52% at the age of two months after inoculation.